Ampliando horizontes sobre medición del rendimiento y regularidad en el baloncesto profesional - Salmeron-Gomez, R.; Gomez-Haro, S. (Revista Internacional de Ciencias del Deporte, 2016)
Get relevant information about players and team performance to take decisions causes a continuous analysis of factors affecting individual and group performance in sport context. The need for positive results takes to use management tools that estimate athletic performance of professional players reliable in regards to the decision by the sport managers, for example, when they are designing the player roster. This study aims to improve the existing analysis by providing, on the one hand, new indexes to measure performance and regularity of professional basketball players, and showing how traditional statistics tools can detect relevant information. We use data from every player in terms of performance according to Spanish basketball league ACB in the 2014/2015 season with a minimum of ten games played and ten minutes averaged per game to redefine and show new elements to consider in assessing the performance of the players. The results obtained have interesting prospects for aspects of sports management as recruiting, roster designing and performance of sports teams.